Technology transfer. Multi-purpose cows for milk, meat and traction in smallholder farming systems. Proceedings of a consultation - Zerbini, E.; Shapiro, Barry I.; Chirgwin, J.C. (International Livestock Research Institute, 1998)
The aim of this consultation is to explore the practicality of extending technologies that enable the use of dairy cows for multiple purposes, to help develop a regional project to transfer these technologies to relevant countries in east and Central Africa. The focus of the consultation is on new technologies developed by the International Livestock Research Institute (ILRI) and the Ethiopian Institute of Agricultural Research (IAR) to help introduce multi-purpose crossbred cows into smallholder production systems, focussing on traction in addition to milk and meat production. Topics of discussion include development of cow traction technologies, social and cultural altitudes towards adoption of cow traction, extension efforts to spread the technology, draft power use in smallholder farming systems, research on the nutrition of cows, and potential and extent of use of cows for draft work. Countries involved in the study include Kenya, Uganda, Tanzania, Malawi, Ethiopia, Mozambique, Indonesia, Philippines, Thailand, Vietnam, China and India.